Milk ejection patterns remain consistent during the first and second lactations. Issue 3 (17th January 2017) - Gardner, Hazel; Kent, Jacqueline C.; Prime, Danielle K.; Lai, Ching‐Tat; Hartmann, Peter E.; Geddes, Donna T.
Abstract: Objective: Milk ejection is a critical physiological process for successful lactation in humans and without it little milk can be removed. Individual milk ejection patterns have been shown to remain consistent between breasts at different lactation stages and using different vacuum patterns with an electric breast pump. Little is known about the milk ejection characteristics during the second lactation period in the same mother. The objective of this study was to examine milk ejection characteristics in the same woman over two lactations. Methods: One mother took part in two pumping studies during consecutive lactations. One pumping study examined milk ejection characteristics during simultaneous breast expression during the first lactation. The second pumping study (second lactation) used two different pumping patterns. Three distinct milk ejections were measured during each pumping session. Results: Measurements of milk flow were used to compare the duration and time taken to reach the peak of each milk ejection for two pumping sessions from each of the lactations. There were no significant differences in milk ejection characteristics between breasts, using different pumping patterns, or between lactations in this mother ( P > .05). Conclusion: Milk ejection appears to be a physiological response that is consistent across consecutive lactations within the same mother. This suggests that milk ejection characteristics are established during or prior to the first lactation. The infant appears to have little influence on the milk ejection characteristics of the mother.